2016
DOI: 10.4049/jimmunol.1601146
|View full text |Cite
|
Sign up to set email alerts
|

CD8αβ+ γδ T Cells: A Novel T Cell Subset with a Potential Role in Inflammatory Bowel Disease

Abstract: full#ref-list-1 , 20 of which you can access for free at: cites 53 articles This article average * 4 weeks from acceptance to publication Fast Publication! • Every submission reviewed by practicing scientists No Triage! • from submission to initial decision Rapid Reviews! 30 days* • Submit online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 53 publications
3
53
0
Order By: Relevance
“…Another study later identified a population of high cytotoxic and immune-regulatory intestinal CD8 + γδ T cells carrying the heterodimer CD8αβ. This latter immunoregulatory subset plays a key role in the homeostasis of gut-associated lymphoid tissue and in the pathogenesis of inflammatory bowel disease (IBD) (26). Our results showed that, while the entire population of CD8 + γδ IELs express significantly higher levels of α rather than β chain, the subset of NKp46 + /CD8 + γδ IELs coexpresses similar levels of α and β chains in their CD8 receptor ( Figure 1F).…”
Section: Resultsmentioning
confidence: 84%
“…Another study later identified a population of high cytotoxic and immune-regulatory intestinal CD8 + γδ T cells carrying the heterodimer CD8αβ. This latter immunoregulatory subset plays a key role in the homeostasis of gut-associated lymphoid tissue and in the pathogenesis of inflammatory bowel disease (IBD) (26). Our results showed that, while the entire population of CD8 + γδ IELs express significantly higher levels of α rather than β chain, the subset of NKp46 + /CD8 + γδ IELs coexpresses similar levels of α and β chains in their CD8 receptor ( Figure 1F).…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies have reported that 20%-30% of peripheral blood γδ Tc are CD8+low, [188,194] expressing CD8α and CD8β polypeptides in all possible combinations, with the largest proportion of cells (44% ± 17%) exhibiting CD8ββ homodimers and smaller fractions expressing CD8αα homodimers (14% ± 12%) or CD8αβ heterodimers (14% ± 12%, and that the mean fluorescence intensity of CD8 expression is much lower in CD8αα and CD8ββ γδ Tc [181]. One study showed that CD8αβ+ γδ Tc were enriched within the gut mucosa comparatively to the PB; they expressed cytotoxic cell-associated markers, such as the CD56 adhesion molecule; and cytotoxic granule proteins, such as granzyme B and perforin; they produced mainly IFN-γ and TNF-α, and, in the PB, they were mostly Vδ1 [195]. This could explain why we observed that in nearly half of the normal PB samples analyzed, part of the Vδ1, but not of Vδ2 Tc, had high and homogeneous CD8 expression, at levels that approximated to those observed in CD8+high αβ Tc.…”
Section: Cd8 Accessory Moleculementioning
confidence: 99%
“…Reports have shown that CD8 + γδ T cells selectively localize to intestinal epithelial tissue and are mostly Vδ1 + [23,24]. Furthermore, a potential role in intestinal inflammatory diseases has been recently described [15]. In line with previous report, we showed that CD8 + γδ T cells are more frequent in CMV+ grafts [25] and express Vγ9γδ T cells.…”
supporting
confidence: 91%